Positron emission tomography/magnetic resonance imaging (PET/MRI): An update and initial experience at HC-FMUSP - Queiroz,Marcelo A. (2018)
Summary The new technology of PET/MRI is a prototype of hybrid imaging, allowing for the combination of molecular data from PET scanning and morphofunctional information derived from MRI scanning. Recent advances regarding the technical aspects of this device, especially after the development of MRI-compatible silicon photomultipliers of PET, permitted an increase in the diagnostic performance of PET/MRI translated into dose reduction and higher imaging quality. Among several clinical applications, PET/MRI gains ground initially in oncology, where MRI per se plays an essential role in the assessment of primary tumors (which is limited in the case of PET/CT), including prostate, rectal and gynecological tumors. On the other hand, the evaluation of the lungs remains an enigma although new MRI sequences are being designed to overcome this. More clinical indications of PET/MRI are seen in the fields of neurology, cardiology and inflammatory processes, and the use of PET/MRI also opens perspectives for pediatric populations as it involves very low radiation exposure. Our review aimed to highlight the current indications of PET/MRI and discuss the challenges and perspectives of PET/MRI at HC-FMUSP.